Can Deep Learning Models Differentiate Atrial Fibrillation from Atrial Flutter? - Ribeiro, Estela; Soares, Quenaz Bezerra; Dias, Felipe Meneguitti; Krieger, Jose E.; Gutierrez, Marco Antonio (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2025)
Atrial Fibrillation (AFib) and Atrial Flutter (AFlut) are prevalent arrhythmias that present similar clinical features, challenging automated ECG differentiation. This study investigates the classification of AFib and AFlut using 12-lead ECGs from the CinC2021 dataset and a private dataset. We evaluated both 1D and 2D deep learning models. For 1D models, LiteVGG-11 demonstrated the highest performance, achieving an Acc of 77.91, AUROC of 87.17, and F1 score of 76.59. For 2D models, the EfficientNet-B2 outperformed other architectures, with an Acc of 75.20, AUROC of 85.50, and F1 of 71.59. Our results show that 1D models outperform 2D ones and that performance varies significantly across datasets, highlighting the difficulty in distinguishing AFib from AFlut.